Hypoglycemia Unawareness in Older Compared With Middle-Aged Patients With Type 2 Diabetes - Bremer, Jan P. (American Diabetes Association, 2009)
OBJECTIVE: Older patients with type 2 diabetes are at a particularly high risk for severe hypoglycemic episodes, and experimental studies in healthy subjects hint at a reduced awareness of hypoglycemia in aged humans. However, subjective responses to hypoglycemia have rarely been assessed in older type 2 diabetic patients. RESEARCH DESIGN AND METHODS: We tested hormonal, subjective, and cognitive responses (reaction time) to 30-min steady-state hypoglycemia at a level of 2.8 mmol/l in 13 older (≥65 years) and 13 middle-aged (39–64 years) type 2 diabetic patients. RESULTS: Hormonal counterregulatory responses to hypoglycemia did not differ between older and middle-aged patients. In contrast, middle-aged patients showed a pronounced increase in autonomic and neuroglycopenic symptom scores at the end of the hypoglycemic plateau that was not observed in older patients (both P < 0.01). Also, seven middle-aged patients, but only one older participant, correctly estimated their blood glucose concentration to be <3.3 mmol/l during hypoglycemia (P = 0.011). A profound prolongation of reaction times induced by hypoglycemia in both groups persisted even after 30 min of subsequent euglycemia. CONCLUSIONS: Our data indicate marked subjective unawareness of hypoglycemia in older type 2 diabetic patients that does not depend on altered neuroendocrine counterregulation and may contribute to the increased probability of severe hypoglycemia frequently reported in these patients. The joint occurrence of hypoglycemia unawareness and deteriorated cognitive function is a critical factor to be carefully considered in the treatment of older patients.